Design of Smart Street Light System for Smart City based on IoT: A Review (International Journal of Innovative Research in Computer Science & Technology, 2021)
Explicit, quantifiable, achievable,  important, and time sensitive are the five parts of the  word Smart. The Internet of Things (IoT) alludes to an  immense and expanding assortment of advanced gadgets  that at present number in the billions and work over  possibly worldwide organizations. Individuals are turning  out to be more attracted to the term smart as the globe  develops speedier. Considering that India is one of the  world's quickest extending economies, we are taking on a  savvy innovation explicitly, a shrewd streetlamp  framework. In any event, when power is free, the manual  streetlamp framework enlightens with full force from  sunset to first light. The saved energy might be utilized  for an assortment of uses, including private, business, and  modern. The LDR sensor is utilized. We can turn a light  on or off in view of the strength of light. The framework's  power source is the primary inventory, which is changed  over through a transfer. Each city requires a road lighting  framework, which is basic. We are utilizing the venture  by means of an IOT module to preserve power.  Everything is transforming into mechanization as the  globe changes drastically. This is a shrewd control  framework that settles on wise choices in light of exact  continuous field information.
Keywords: Automation; Arduino UNO; ESP8266 Wi-Fi Module; IoT; LDR